2017
DOI: 10.3389/fimmu.2017.01871
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Membrane-Bound CC Chemokine Ligand 20 on Follicular T Helper Cells in T–B-Cell Conjugates

Abstract: The CC chemokine receptor 6 (CCR6) and its sole chemokine ligand CC chemokine ligand 20 (CCL20) display an emerging role in the coordination of humoral immune responses. Recent studies demonstrate a role of this chemokine axis in the migration of B cells to key immunological sites during an immune response, and facilitating the generation of high-quality antibodies. Very little, however, is known about CCL20 and its role in these functions. We undertook a preliminary investigation into the expression and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Further antibodies: CD3 (clone 145-2C11), CD8α (clone 53-6.7), CD11b (clone M1/70), CD11c (clone N418), CD45 (clone 30-F11), CD138 (clone 281-2), F4/80 (clone BM8), Fas (clone 15A7), Ly6c (clone HK1.4), Ly6G (clone 1A8), MHCII (clone M5/114.15.2), TACI (clone ebio8F10-3), and Siglec F (clone ES22-10D8), PNA-biotin (Vector), Streptavidin-PE/CF594 (BD), NKp46 (clone 29A1.4), CD49 (clone DX5), CD16 (clone 93), IL-4 (clone 11B11), IL-17 (clone TC11-18H10.1), IL-9 (clone RM9A4). T FH :B cell doublet gating strategy is adopted from previously published article 69 and is shown in Supplementary Fig. 3f.…”
Section: Methodsmentioning
confidence: 99%
“…Further antibodies: CD3 (clone 145-2C11), CD8α (clone 53-6.7), CD11b (clone M1/70), CD11c (clone N418), CD45 (clone 30-F11), CD138 (clone 281-2), F4/80 (clone BM8), Fas (clone 15A7), Ly6c (clone HK1.4), Ly6G (clone 1A8), MHCII (clone M5/114.15.2), TACI (clone ebio8F10-3), and Siglec F (clone ES22-10D8), PNA-biotin (Vector), Streptavidin-PE/CF594 (BD), NKp46 (clone 29A1.4), CD49 (clone DX5), CD16 (clone 93), IL-4 (clone 11B11), IL-17 (clone TC11-18H10.1), IL-9 (clone RM9A4). T FH :B cell doublet gating strategy is adopted from previously published article 69 and is shown in Supplementary Fig. 3f.…”
Section: Methodsmentioning
confidence: 99%
“…CCR6 and CCL20 may assist with positioning T FH and B cells at the T-B cell border and contributing to the "quality" of the T-B cell synapse. 8 The role of the possible raised CCR6 on B-cell subsets in SLE patients 66 remains a mystery at this stage. However, Elgueta et al 75 have shown that CCR6 expression on memory B cells remains important for proper localization and function of these cells in lymphoid organs, and CCR6 has been identified as a marker of B cells undergoing memory B-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a small percentage of T FH cells have been shown to be CCR6 + . 8 In SLE studies, circulating T FH cells-rather than tissue T FH cells-have been commonly studied owing to ease of acquisition. They are thought to have originated from, and be functionally similar to, their GC compartment counterparts, although have discernible differences in their epigenetic profile.…”
Section: Follicular Helper T Cells and Subsetsmentioning
confidence: 99%
See 2 more Smart Citations